Early relapse following sagittal split advancement - Richard Hing N. (Sciendo, 1989)
Early relapse following bilateral sagittal split advancement (BSSA) was assessed by evaluating the cephalograms of 47 patients. The records were assigned to either screw fixation (SF: n=25) or wire osteosynthesis (WF: n=22) groups and subdivided if additional Le Fort I osteotomy was performed. 9 skeletal parameters were evaluated. The results showed that there were relatively minor differences between the screw and wire osteosynthesis groups in the first 6 weeks following surgery. Relapse of 11 percent and 22 percent was recorded respectively but this difference was not statistically significant.